Foliar application of Kappaphycus alvarezii extract improves drought tolerance in wheat (Triticum aestivum) by modulating physiologicaland biochemical responses - MEENA, SHASHI; TARIA, SUKUMAR; SEKAR, KOUSALYA (The Indian Journal of Agricultural Sciences, 2026)
The study was carried out during the winter (rabi) season of 2023–24 and 2024–25 at ICAR-Indian Agricultural Research Institute, New Delhi to reveal the potential of Kappaphycus alvarezii extract (KE), applied as Sagarika concentrate liquid in enhancing drought tolerance in wheat (Triticum aestivum L.). In this study, plants were subjected to foliar sprays of KE at varying concentrations (2.5%, 7.5%, and 10% v/v) and exposed to short-term drought stress (10 days) during initial vegetative phase (one-month old wheat seedlings). The results revealed that KE application significantly improved plant performance and physiological parameters under water stress conditions. The treatment combining irrigation with 10% KE (T5) recorded the highest soil moisture content (29.17%) and shoots biomass (1.858 g DW/plant) while drought-stressed plants without KE (T2) showed the lowest values. KE-treated plants retained higher relative water content, membrane stability and chlorophyll levels indicating improved stress tolerance. In addition, cellular oxidative stress markers such as electrolyte leakage and hydrogen peroxide accumulation were notably reduced in KE-applied treatments, confirmed through both biochemical analysis and DAB staining. These findings suggest that KE foliar application enhances drought resilience in wheat by alleviating oxidative stress and supporting physiological stability making it a sustainable and eco-friendly strategy for improving crop growth responses under water-deficit conditions.